2023
DOI: 10.1177/17562848231170484
|View full text |Cite
|
Sign up to set email alerts
|

The efficacy of immune checkpoint inhibitors in biliary tract cancer with KRAS mutation

Abstract: Background: With a 15% incidence, KRAS is one of the most common mutations in biliary tract cancer (BTC) and is a poor prognostic factor. Immune checkpoint inhibitors (ICIs) as salvage therapy have modest activity in BTC. Objectives: There are limited data on the efficacy of ICIs according to KRAS mutation in BTC. We evaluated the efficacy of ICIs in BTC patients with or without KRAS mutations. Design: Retrospective observational study. Methods: We conducted molecular profiling in BTC patients who received ICI… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 22 publications
0
3
0
Order By: Relevance
“…The results showed that GBC had a relative higher mean and median TMB and proportion of PD-L1 high expression, which are favorable factors for ICI therapy response in KRAS -mutated GBC . In a 2023 study by Jeong et al, patients with KRAS allelic variants and PD-L1 positivity had a longer progression-free survival than patients with KRAS allelic variants and PD-L1 negativity. Preclinically, KRAS inhibitors have been associated with promotion of a proinflammatory tumor microenvironment, increased major histocompatibility complex class I protein expression, and synergies with immunotherapy to enhance antitumor activity .…”
Section: Discussionmentioning
confidence: 99%
“…The results showed that GBC had a relative higher mean and median TMB and proportion of PD-L1 high expression, which are favorable factors for ICI therapy response in KRAS -mutated GBC . In a 2023 study by Jeong et al, patients with KRAS allelic variants and PD-L1 positivity had a longer progression-free survival than patients with KRAS allelic variants and PD-L1 negativity. Preclinically, KRAS inhibitors have been associated with promotion of a proinflammatory tumor microenvironment, increased major histocompatibility complex class I protein expression, and synergies with immunotherapy to enhance antitumor activity .…”
Section: Discussionmentioning
confidence: 99%
“…Though RAS mutations have been reported in 37% of patients with eCCA, actionable RAS mutations such as KRAS G12C are much rarer, occurring in 1–2% of BTC [ 25 •, 114 ]. The phase II KRYSTAL-1 trial [ 94 ] evaluated adagrasib, an oral KRAS G12C irreversible inhibitor, in 12 patients (21% of study population) with BTC.…”
Section: Advanced Stage Diseasementioning
confidence: 99%
“…Interestingly, this finding is not discovered in patients without KRAS mutation. 222 Fatty acid-binding protein 1 (FABP1) is reported to induce the uptake of fatty acids to mediate lipid metabolism of cancer cells during metastasis. 223 The expression of FABP1 is significantly higher in direct liver invasion tumor than in primary tumor of GBC and is associated with lymph node metastasis and OS.…”
Section: Ici Combination Trialsmentioning
confidence: 99%